Electronically tunable MOS-only current-mode high-order band-pass filters - Prommee, Pipat; Tiamsuphat, Aphinat; Taher Abuelma'Atti, Muhammad (My University, 2017)
This paper presents new CMOS current-mode ladder Chebyshev and elliptic band-pass filters (BPFs). The signal flow graph and the network transformation methods are used to synthesize the proposed BPFs by using Chebyshev and elliptic RLC low-pass prototypes. CMOS-based lossy and lossless integrators with grounded capacitors are used to synthesize the proposed BPFs. The proposed filters can be electronically tuned between 10 kHz and 100 MHz by adjusting the bias current from 0.02 A to 200 A. Both filters use a 1.5 V DC power supply, which leads to low dynamic power consumption. Both filters enjoy total harmonic distortion of less than 1.5% along the range of the tuning bias currents. Simulation results are included to illustrate the functionality of the proposed filters.
Keywords: Band-pass filter; Chebyshev; CMOS; Current mode; Elliptic; Ladder filters